Effects of entry conditions on channel flow characteristics (2021)
There have been various studies on channel flow due to its relevance in engineering applications, but the effects of the entry conditions on its flow characteristics have not been given much attention. This 2-D numerical simulation studied how the initial velocity and tripping devices at the entrance of a channel affect the mean flow structure. The CFD analysis is based on the use of COMSOL Multiphysics. The turbulent stresses in the RANS equation are closed using the k-ɛ turbulence model. Input parameters for the simulation are taken from experimental conditions in the literature, with Reynolds number ranging from 18,700 to 600, 000. The CFD strategy flow without tripping is validated against experimental results and a good agreement is achieved. The results show that the skin friction factor for the flow without tripping for Reynolds number 18,700 is 3.59x10-3. However, for the same Re, with tripping devices covering 15%, 30%, 45%, and 60% of the channel height, the skin friction factors are 3.68x10-3, 3.78x10-3, 3.82x10-3, and 3.98x10-3 respectively. Hence it has been shown the tripping devices placed at the entry of a channel increase the skin friction coefficient by values between 2% to 11% for the various conditions considered in this work.